Diagnostic implications of lncRNA NORAD in breast cancer - Yaping Zhang; Xiaowei Fan; Jianfeng Hong; Enyu Yang; Cheng Xuan; Hongming Fang; Xianfeng Ding (Scientific Reports, 2023)
Abstract This study aimed to assess the expression levels of non-coding RNA activated by DNA damage (NORAD) in the cells, tissues, and serum of breast cancer (BRCA) patients and benign breast nodules and investigate its association with clinicopathological characteristics and prognosis in BRCA. NORAD was analyzed using TCGA-BRCA, GSE77308, Cellminer, and Sangerbox databases, revealing its significance in BRCA prognosis, immune microenvironment, and cell function. Serum samples from 38 BRCA patients, 80 patients with benign breast nodules (50 fibroadenoma and 30 breast adenosis cases), and 42 healthy individuals were collected from Zhejiang Xiaoshan Hospital. NORAD expression was quantified using quantitative reverse transcription PCR (RT-qPCR). Differential NORAD expression between benign and malignant breast nodules and its relationship to clinicopathological characteristics were assessed. NORAD demonstrated elevated expression in BRCA patient serum compared to healthy individuals and those with benign breast nodules (P < 0.05). Moreover, its expression correlated with TNM-stage, lymph node metastasis, and luminal classification. These findings highlight the elevated NORAD expression in BRCA patient serum and its correlation with clinicopathological characteristics, providing insights into its potential as a diagnostic biomarker or therapeutic target.